Осушитель воздуха на элементе Пельтье; Вестник науки Сибири; № 15 : Спецвыпуск - Мусоров И. С. Илья Сергеевич; Торгаев С. Н. Станислав Николаевич; Чертихина Д. С. Дарья Сергеевна; Евтушенко Г. С. Геннадий Сергеевич; Огородников Д. Н. Дмитрий Николаевич; Царева Т. В. Татьяна Викторовна (Инженерные науки, 2015)
Заглавие с титульного листа